2008
DOI: 10.1007/978-3-540-88961-8_18
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking for Steganography

Abstract: Abstract. With the increasing number of new steganographic algorithms as well as methods for detecting them, the issue of comparing security of steganographic schemes in a fair manner is of the most importance. A fair benchmark for steganography should only be dependent on the model chosen to represent cover and stego objects. In particular, it should be independent of any specific steganalytic technique. We first discuss the implications of this requirement and then investigate the use of two quantities for b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(22 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…We also observed that as we lowered the compression quality of JPEG images, there was a decrease on the number of pixels located in high complexity sub-domains. JPEG compression removes high frequency details from images as considered by Pevny and Fridrich [8]. Furthermore, the number of image artifacts increases as we lower the compression quality.…”
Section: Resultsmentioning
confidence: 99%
“…We also observed that as we lowered the compression quality of JPEG images, there was a decrease on the number of pixels located in high complexity sub-domains. JPEG compression removes high frequency details from images as considered by Pevny and Fridrich [8]. Furthermore, the number of image artifacts increases as we lower the compression quality.…”
Section: Resultsmentioning
confidence: 99%
“…Then, the relative payload is fixed to 0.2bpp in order to reduce the complexity of the grid optimization method. The undetectability is evaluated by Maximum Mean Discrepancy [12]. The experimental results of the grid optimization method are shown in Table 1.…”
Section: Initialization Of Parametersmentioning
confidence: 99%
“…MMD has been used for benchmarking the security of steganography schemes, 14,15 but here it is simply a measure for comparing two actors' sets of feature vectors. It is ideal for our purposes because it can be estimated, even for very high dimensional vectors, from relatively few empirical samples: given n observations x = (x 1 , .…”
Section: Maximum Mean Discrepancy (Mmd)mentioning
confidence: 99%